CAMELINA SATIVA AS A CROP FOR DIVERSIFICATION OF AGRICULTURE AND AS A PRODUCER OF HIGH QUALITY OIL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
‘Camelina sativa’ is one of the oldest oil crops in Europe. Growing areas were reduced dramatically in 20-40-ties of the last century. Low price of rape oil and unclear composition of camelina oil were primary reasons of this process. Nevertheless, last years ‘Camelina sativa' attracted a great interest of scientists and oil processors as a crop for diversification of agriculture and, in the same time, for producing of the high quantity and quality oil for biofuel, feeding, food, and pharmacy (source of a-linolenic acid, linoleic acid and vitamins, especially E). In Latvia ‘Camelina sativa' is spread as a wild form but for the agriculture it is a new crop.The potential of me of ‘Camelina sativa’ in the Latgale region as an alternative oil crop and a new plant in the crop rotation was investigated. We compared the oil content and it composition in ‘Camelina sativa ’ seeds from plants of variety ‘Ligena’ grown in different conditions (Latvia and Germany). We also are looking for a possibility to use biotechnology methods for obtaining additional camelina breeding source material. For this purpose we applied calli culture method for producing plants-regenerants.